PEMIKIRAN POLITIK FEMINISME DALAM SERIAL DRAMATHE KING TWO HEARTS - Putri Wahyu Amar Pratiwi; Dwi Wahyu Handayani; Ari Darmastuti (Metakom, 2020)
Feminism campaigns have been done through various media, one of which is audiovisual media. The audio-visual media has asignificant influence in constructing the mindset of communitymembers, especially women. This study aims to analyze the content of feminist political thought in an audio-visual media. This research describes the feminist political thinking contained in The King Two Hearts Drama Series through the characterization of Kim Hang-Ah. The King Two Hearts Drama Series was chosen because of the high interest of Indonesian women in the South Korean drama series. This studyappliedthe theory of semiotics with descriptive qualitative research methods. The study found three important aspects that illustrate the feminist political thinking in The King Two Hearts Drama Series, those are: 1) Kim Hang Ah as a rational, physically and mentallystrong, inteligence and a high self-confidentwoman; 2) Kim Hang-Ah's decision-making ability as asubject, rational and common good oriented; 3) Kim Hang-Ah's ability to dominate others and willing to be dominated for common good. In addition, this drama series alsofunctions as acampaign of feminism against patriarchal culture through the content it presents. Thisdrama seriesportrays aPostmodern Feminismschool of thought.